Assessment and Investigation of Science Learning Environments in the Early Childhood Grades - Peiro, Maria; Fraser, Barry (Nova Publishers, 2009)
This study involved the development of modified English and Spanish ' versions of the Constructivist Learning Environment Survey (CLES) and the Test Of Science-Related Attitudes (TOSRA) and their validation and use among 739 students in Grades K-3 in two schools in Miami, Florida. Analyses supported the sound factor structure and internal consistency reliability of the scales and revealed strong, positive and significant relationships between the science classroom environment and students' attitudes toward science. A teacher action research project supported the effectiveness of a three month intervention in terms of significant pre-post differences for CLES, TOSRA and achievement scales. Effect sizes indicated large and educationally important changes in classroom environment, science understanding, and attitudes toward science.